2019
DOI: 10.1108/nfs-07-2018-0218
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition risk and perception on dietary practices among elderly living in agricultural settlements

Abstract: Purpose: This research aims to identify malnutrition risk and perception of malnourished and at-risk elderly individuals on their dietary practices. Design/methodology/approach: In Phase 1, a cross-sectional study was conducted among 413 elderly individuals aged 60 years and above in agricultural settlements in Kuantan, Pahang, Malaysia. Malnutrition risk was assessed using the Mini Nutritional Assessment Short-Form (MNA-SF). In Phase 2, indepth semi-structured interviews were conducted among 21 elderly indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…However, it should be noted that our findings demonstrated a deficiency in key nutrients among the elderly in the agricultural settlement, which showed a need for appropriate nutrition education. Moreover, a recent study among this population in the same setting demonstrated the existence of malnutrition risk (Zainudin et al, 2018). Maintenance of good nutritional status while living independently at home should be targeted while promoting longevity along with the quality of life.…”
Section: Discussionmentioning
confidence: 89%
“…However, it should be noted that our findings demonstrated a deficiency in key nutrients among the elderly in the agricultural settlement, which showed a need for appropriate nutrition education. Moreover, a recent study among this population in the same setting demonstrated the existence of malnutrition risk (Zainudin et al, 2018). Maintenance of good nutritional status while living independently at home should be targeted while promoting longevity along with the quality of life.…”
Section: Discussionmentioning
confidence: 89%
“…15 In addition, studies conducted in Malaysia have found that older adults residing in agricultural settlements are at malnutrition risk. 16,17 The results of the current study show that mean body mass index was the highest for older men and women living in FELDA settlements, indicating that being overweight or obese may increase the risk of sarcopenia and the resulting vulnerability to diseases and physical decline.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown percentages of 27% to 38% of older adults at risk and malnourished in community setting (Kaiser et al, 2010;Volkert et al, 2019;Winter et al, 2013). Meanwhile, in Malaysia's community setting, the prevalence of malnutrition is between 34.0% to 48.9% and 42.2% to 66.6% of male and female older adults, respectively, having risk of malnutrition (Muhamad et al, 2019;Suzana et al, 2013;Zainudin et al, 2019). If malnutrition is left untreated, it will lead to undesirable health effects.…”
Section: Introductionmentioning
confidence: 97%